1987
DOI: 10.1139/z87-448
|View full text |Cite
|
Sign up to set email alerts
|

Growth and physiological condition of black ducks reared on acidified wetlands

Abstract: Acid deposition has been identified as one of several possible factors contributing to the decline of some waterfowl populations in North America. In an effort to examine the effects of acidification on black duck (Anas rubripes) recruitment, growth and physiological condition were monitored in ducklings foraging for a 10–day trial (days 10–20 of life) on acidified (pH 5.0) and circumneutral (pH 6.8) fish-free emergent wetlands. Acidification of these wetlands suppressed phytoplankton and algal growth, and red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Svensson and MerilaÈ (1996) found that birds with high levels of subcutaneous fat had high haematocrit values and low sedimentation rate levels, indicating that the haematocrit level of an individual is associated with its nutrition and state of health. Rattner et al (1987) reported positive correlations between haematocrit and weight change during growth in ducklings. We found that¯edglings in good condition as scored by their mass and development of breast muscles also had high haematocrits which were, however, unrelated to another measure of growth performance, tarsus length (Alatalo and Lundberg 1986;Potti and Merino 1994;Moreno et al 1997).…”
Section: Discussionmentioning
confidence: 96%
“…Svensson and MerilaÈ (1996) found that birds with high levels of subcutaneous fat had high haematocrit values and low sedimentation rate levels, indicating that the haematocrit level of an individual is associated with its nutrition and state of health. Rattner et al (1987) reported positive correlations between haematocrit and weight change during growth in ducklings. We found that¯edglings in good condition as scored by their mass and development of breast muscles also had high haematocrits which were, however, unrelated to another measure of growth performance, tarsus length (Alatalo and Lundberg 1986;Potti and Merino 1994;Moreno et al 1997).…”
Section: Discussionmentioning
confidence: 96%
“…A positive relationship between cholesterol and body mass has been described in growing black ducks (Anas rubripes) in artificially poor ecological conditions (Rattner et al 1987). However, in other gull species cholesterol remained stable during fasting, pathological processes, and migration (Jeffrey et al 1985;Averbeck 1992;Cantos et al 1994).…”
Section: Changes In Other Biochemical Traits Throughout the Experimentsmentioning
confidence: 99%
“…Blood chemistry measurements were selected that have been indicators of developmental toxicity as well as delayed growth in mallard ducklings (Hoffman et al 1982;Fleming et at. 1985;Rattner et al 1987;Hoffman 1988) and in nestling birds (Hoffman et al 1985. The following plasma enzyme activities were measured: alanine aminotransferase (ALT; EC 2.6.1.2), alkaline phosphatase (EC 3.1.3.1), aspartate aminotransferase (AST; EC 2.6.1.1), creatinine kinase (CK; EC 2.7.3.2), 2~-glutamyl tranferase (y-GT; EC 2.3.2.2.…”
Section: Collection Of Tissues and Measurements O F Blood Chemistriesmentioning
confidence: 99%